Assessment of the impact of technology transfer through the purchase of plant and equipment : three cases in the Shanghai electroniccs industry - Tang, Jinyan; Ramanathan, K.; Sharif, N.; Swierczek, F.W.; French Government (Bangkok : Asian Institute of Technology, 1992)
The objective of the study is to assess the impact that purchasing plant and equipment can have on indigenous technological capabilities of the Shanghai Electronics Industry. For purposes of t his study only impact on production capabilities and human resources capabilities have been examined . To attain this obj ective the study uses a simple multi-indicator approach to assess the changes of t echnology capability before and after the purchasing of plant and equipment. To apply the framework developed, studies were carried out three companies i n the Shanghai Electronics Industry. Interviews with senior managers and officers, dealing with technological decisions, were conducted . A questionnaire wa s used for thi s purpose. The impact of the policy environment in the development of these capabilities was also examined. Based on the finding s some recommendations are made for improving the eff ectiveness of the capability upgradation process .
A research study submitted i n partial fulfillment of the requirements for the degree of Master of Business Administration.
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 1992
Keywords: Technology transfer -- China -- Shanghai; Electronic industries -- China -- Shanghai